Ethical Governance in the Age of Artificial Intelligence:Challenges and Opportunitiesfor the Western Balkans - Marsili, M. (4th International Social Science Week, International Roundtable on Development and Challenges in the Western Balkan: Regional and European Models, 2025)
This presentation explores the ethical and political implications of Artificial Intelligence (AI) in the context of governance, with a focus on the Western Balkans. As AI technologies increasingly influence decision-making processes, it is crucial to address the ethical challenges they pose, particularly in regions undergoing political and social transformation. Drawing on contemporary political philosophy and ethical theory, this talk will examine how AI can both enhance and undermine democratic governance, transparency, and accountability. The presentation will also propose frameworks for ethical AI integration in public policy, emphasizing the need for regional cooperation and interdisciplinary approaches to ensure that technological advancements align with democratic values and human rights.